Aligning Climate Policy with National Interest: Disengagements with Nationally Appropriate Mitigation Actions in South Africa. Issue 4 (7th August 2016) - Upadhyaya, Prabhat
Abstract: Nationally Appropriate Mitigation Actions (NAMAs) were proposed as a policy framework that could provide middle ground for meeting both the development and mitigation objectives in developing countries. While South Africa engaged actively with the NAMA terminology in the United Nations Framework Convention on Climate Change negotiations, its engagement at the domestic level has been rather lacklustre. This presents an interesting paradox. The paper studies the interplay of international norms embodied in NAMAs with South Africa's domestic policy process. Disengagement and contestation around NAMAs in South Africa is played out at three stages: decision-making stage where the symptoms surrounding this contestation first emerge; policy formulation stage where NAMAs have to not only align with the National Development Plan but also compete with a predilection for domestically familiar terminology of flagships under the national climate policy; and finally the broader agenda-setting stage of policy process, where NAMAs have to prove useful in not only pursuing the developmental state agenda but also in tackling the underlying material factors that represent country's economic dependency on fossil fuels. NAMAs faced combined resistance from ideas and interests in various degrees at all these stages resulting in their disengagement.